(untitled) (Strathmore Law Journal, 2020)
All knowledge is value-laden, influenced by the multifarious inarticulate major premises deriving from our inescapable ideological baggage. However, on occasions such as this, it behooves all people of good sense and logic to endeavour to be objective in their views. Occasions such as these, call upon us to question our own assumptions. We are required to turn our version of logic upside down, inside out, in a critical and evaluative sense. The purpose of all these is to establish a broad spectrum of objectivity that informs the ideas being presented. Part of my observations and verdicts in the analytical aspects of the paper have been rather unflattering—perhaps harsh. That is what we do in the academy. But I guess, they are only but that part of the labour pains we have submitted ourselves to in the birth of a new jurisprudential trajectory for the CoA—a coherent and predictable jurisprudence.